PREPARASI DAN KARAKTERISASI BIOMASSA KULIT PINANG DAN TEMPURUNG KELAPA MENJADI BRIKET DENGAN MENGGUNAKAN TEPUNG TAPIOKA SEBAGAI PEREKAT - Erna Frida; Darnianti Darnianti; Jamal Pandia (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2019)
This study conducted the preparation and characterization of charcoal briquettes originating from areca nut skin biomass and coconut shell using tapioca flour as an adhesive. Stages of preparation are cleaning, carbonization, densification, and characterization. Characterize by measuring the level of water, dust, and bound carbon. The characterization results showed that the briquette's water content ranged from 4.1% - 6.9%, ash content was 2.4 - 5.8%, and carbon content was bound to 44% - 60.9%. This result is by SNI No.01-6235-2000. So it can be useful as an alternative fuel.